UPAYA PEMERINTAH NAGARI DALAM MENANGANI BALAP LIAR DI NAGARI PARIT MALINTANG KECAMATAN ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Aprilia, Gita; Elfemi, Nilda; Yuhelna, Yuhelna (Universitas Tanjungpura, 2022)
Illegal racing is a delinquency that often occurs in the community, and is very disturbing in the community, of course efforts are needed to overcome this delinquency, it can be done by the nagari government, because it is the main authorized institution in society. The purpose of the research is that the Nagari Government can make efforts to deal with illegal racing in Nagari Parit Malintang, Six Lingkung District, Padang Pariaman Regency. The theory used in this research is the Structural Functional Theory proposed by Talcott Parsons. The research was conducted in Nagari Parit Malintang, Enam Lingkung District, Padang Pariaman Regency. This research used qualitative research methods with descriptive research type. The withdrawal of informants was carried out by purposive sampling technique. The data collection method in this study began with observation, in-depth interviews, and document studies. Data analysis techniques in research can be carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that there have been efforts made by the nagari in overcoming the illegal racing that occurred including: 1) Providing socialization or counseling to the community. 2) Conducting patrols or raids and 3) Guarding the location where the illegal race took place.